PROYECTO PARA LA CREACIÓN DE UNA EMPRESA DEDICADA AL SERVICIO DE CATERING A DOMICILIO EN LA CIUDAD DE LOJA - JARAMILLO CÓRDOVA, ANDREA ALEXANDRA (2020)
The present research work called: "Project for the creation of a company dedicated to the catering service at home in the city Loja"; It was carried out in the city of Loja, which has the purpose of implementing a company that allows creating work sources, taking advantage of existing resources and putting into practice the knowledge acquired, for the benefit of society that needs its new professionals they are inserted in the productive and economic life. For the elaboration of the project, research methods and techniques were used such as: the inductive, deductive and descriptive method, as techniques, direct observation, bibliographic compilation and the survey were used; through which a sample of 397 surveys applied to the local families was determined; the results of the survey were tabulated, graphed and interpreted, in the same way surveys were applied to the offer to the 5 local companies that offer the service; data that allowed to establish the corresponding conclusions and recommendations. Through the information that was obtained from the surveys, the corresponding studies could be carried out: within the market study, the existing supply and demand was determined, the installed capacity and the used capacity of the project were determined, with the market study some were established marketing techniques focused on the marketing mix such as the 4P (product, price, place and promotion) that will allow the future company to position itself in the market of the city of Loja, through a marketing plan it is intended to introduce the market The product / service offer. With the technical study the size and location of the company was determined, the installed capacity that the company will have being 72,800 dishes per year and a used capacity of 58,240 dishes per year, as well as the best location within the city, the same as It is located in the Citadel Clodoveo Jaramillo, since it has the conditions for a company in this category to 5 develop easily. During the life cycle of the company, it will generate jobs, each activity that the employee performs will have a specific process and time to fulfill their functions. Within the administrative study the organic-functional structure of the company was determined with their respective organizational charts and the manual of functions necessary for the execution of the project, in this study the flowchart of processes and times as well as the balance of materials are also involved. It was established as a Sole Responsibility Limited Liability Company. The study determined the financing of the project, which comes from two sources, an internal one amounting to $ 52.127,75 corresponding to 72,27% and the external one of $ 20,000.00 corresponding to 27,73% of investment through a loan Bank financed through BanEcuador with 11.26%. In the financial evaluation, the feasibility is determined through the financial indicators, obtaining positive results for the implementation of the company, such as the NPV of US $ 31.017,86, which demonstrates that the project is viable, the IRR is greater than the cost of capital with a percentage of 33,12%, in the RBC it is $ 0.20 for every dollar invested, in the PRC it is capital recovered in 3 years, 4 months and 17 days, in the Sensitivity Analysis the project resists an increase in costs up to 11.93% and a decrease of 10.21% in their income.